Growing Up in the Forest. Ethnographic study on Mbya childrearing values and practices. - Remorini, Carolina (2016)
Although some cultural analyses still use simplistic dualisms such as collectivism vs individualism or interdependence vs autonomy, a balance between individual and collective goals and values is noticeable in many Indigenous communities. Mbya Guarani perspectives on children?s growth and development, emphasizes the balance between interdependence and autonomy as complementary values. This article examines the ideas of reciprocity, respect, autonomy, and interdependence of lives and the impact of these on children?s development and health. Using an ecological perspective that recognizes humans? relationship with other living beings that inhabit the forest, this article is based on ethnographic research conducted in two Mbya Guarani communities (Argentina). Respect and reciprocity are key for children to develop as part of thecommunity and the forest and they are related to children´s wellbeing and health. I describe Mbya perspectives on children?s growth and development, providing examples of environmentally relevant skills to grow up in the forest. These skills are associated with particular ways of inhabiting the forest, including learning how to walk in it and developing entendimiento (understanding). These make possible children?s integration incommunity life through their participation and collaboration in daily activities.